Skala Penundaan Umum yang Berasal dari Unintentional Procrastination Scale: Apakah Sudah Layak Digunakan? - Jeff Dean Mozes; Johana Endang Prawitasari (Fakultas Psikologi Universitas Sanata Dharma, 2021)
Skala Penundaan Umum (SPU) has been adopted and modified from Unintentional Procrastinational Scale. Participants of this study were students and nonstudents, females and males. The total number of participants were 201 from mostly Java and some were from other places in Indonesia. Method used to test the SPU were construct, content, and convergent validities, test-retest reliability, and Alpha Cronbach reliability. Results indicated that the SPU was valid and reliable with some cautiousness when it was to be used directly in practice, since there were some limitations in the process of modifying and analyzing the data. The purpose of this article is to discuss whether the scale is proven to being valid and reliable to be used to predict procrastination in general public.